Workplace Lactation Education with Short Videos to Improve Knowledge, Attitudes, and Support - Noor Azizah; Hanifa Maher Denny; Mateus Sakundarno Adi; Sulistiyani Sulistiyani (The Indonesian Journal of Occupational Safety and Health, 2026)
Introduction: Exclusive breastfeeding among women who return to work remains below global recommendations set by the World Health Organization, largely due to persistent psychological and structural barriers. Partner involvement and digitally delivered health education, particularly short-form video content, have been suggested as promising strategies to support breastfeeding continuation among working mothers. This study aimed to evaluate the effectiveness of a workplace-based couple lactation education program with short-form video reinforcement on husbands' breastfeeding knowledge, attitude, and supportive behaviors. Methods: A quasi-experimental pretest–posttest design with a control group was conducted among 84 third-trimester pregnant women (42 intervention, 42 control) employed in the industrial sector of Kudus Regency. The intervention consisted of structured workplace lactation classes involving couples and short-form TikTok videos delivered by a certified lactation counselor. Participants were followed up at one, three, and six months postpartum using validated instruments. Data were analyzed using an independent t-test and General Linear Model Repeated Measures (GLM-RM). Results: The intervention was associated with significant and sustained improvements across outcomes. Husband’s knowledge increased significantly from the third to the six month postpartum (p<0.001). Attitudes improved in the first month (p<0.001), while supportive behaviors showed significant gains at three months and continued to strengthen at six months (p<0.001). GLM-RM analyses indicated significant time effect and group-by-time interactions for all measured outcomes (p<0.05). Conclusion: Short-form video reinforcement, combined with husband-focused lactation education and digital reinforcement into workplace health policies, alongside provisions such as lactation rooms and protected breastfeeding breaks, may support exclusive breastfeeding among working mothers.